PENCARIAN LINTASAN TERPENDEK DENGAN ALGORITME DIJKSTRA DAN MINIMUM SPANNING TREE DENGAN ALGORITME SOLLIN TERHADAP PERJALANAN WISATA SEJARAH DI KABUPATEN SUMENEP - LIKA HANIFA; LUH PUTU IDA HARINI; G.K. GANDHIADI (E-Jurnal Matematika, 2025)
A graph is a diagram that contains specific information.  One concept in graphs that can solve real-life problems is the concept of trees, which consists of various types of trees used to solve problems in life, such as finding the minimum path using the Dijkstra algorithm and the use of minimum spanning trees using the Sollin algorithm. This research produced the minimum path using Dijkstra's Algorithm and the minimum spanning tree using Sollin's Algorithm, which were applied to historical tourist routes in Sumenep Regency.